PEMBELAJARAN RELIGIOSITAS PENDIDIKAN AGAMA ISLAM PROSES PEMBELAJARAN DALAM INTERAKSI EDUKATIF - Hasibuan, Nasruddin (AIN Padangsidimpuan, 2014)
This paper aims to determine the religiosity learning Islamic education, so as to reduce violent behavior among students. Method used in this paper is a method of library research. From the discussion, it can be concluded that the failure of Islamic religious education in growing religiosity, suggesting that Islamic education learning practices in schools held less qualified. Learning developed over the years is invariably puts the teacher as a learning center so that the target is the provision of science learning (transfer of knowledge), the delivery of learning is more normative text . Islamic religious education materials are still a lot going on with the repetition rate of the previous and Islamic religious education materials studied separately and loose relation to other fields of study. Learning methodology presented some teachers statically - indoctrinatif - doctrinaire with cognitive busy main focus in teaching and religious regulations. The pattern of religious education is still concerned with the letter of the spirit, a more literal interpretation precedence over love. So that religiosity or religious learning which should be formed through religious education neglected or failed to be realized . Reality is giving a signal that the implementation of Islamic religious education in schools face a number of urgent problems to be solved in order to be the primary mission carried out by the Islamic religious education to achieve the target